Atypical Exophytic Retinal Capillary Hemangioma and Diagnostic Modalities. Issue 1 (January 2016) - Shechtman, Diana L.; Gold, Aaron S.; McIntosh, Samantha; Steen, Jessica; Murray, Timothy G.
ABSTRACT: Purpose: Retinal capillary hemangioma (RCH) can occur in isolation or may be associated with von Hippel–Lindau disease. The classic RCH is described as a globular reddish lesion with a dilated feeding artery and a tortuous draining vein, indicative of a common endophytic growth pattern. Exophytic patterns are far more rare and, because of its subtle appearance, often missed or misdiagnosed. Case Report: A 24-year-old woman presented with complaints of a mid-peripheral superior field defect OS. She had no family history of von Hippel–Lindau disease. Best-corrected visual acuity was 20/20 OD, OS. Dilated fundus examination of the left eye revealed a peripheral large inferotemporal retinal lesion with an overlying vascular network. Corresponding feeding and draining vasculature was not clearly noted on dilated fundus examination. Optical coherence tomography, ultrasonography, and fluorescein angiography testing were used to confirm the diagnosis of an exophytic peripheral RCH. Anti–vascular endothelial growth factor injections and cryotherapy were initiated, and the patient was scheduled for radioactive plaque brachytherapy. Genetic testing and proper scans were also recommended. Conclusions: This case illustrates an atypical exophytic peripheral RCH, rarely reported in the literature. The utilization of a variety of diagnostic modalities was highly effective, aiding in the diagnosis of this condition.